Estudo de dosimetria e qualidade de imagem em varreduras de tomografia computadorizada de cabeça utilizando objeto simulador - Alvaro Mauricio Ladino Gomez (2017)
Diagnostic images of computed tomography generate higher doses than those generated by other methods of diagnostic radiology using X-ray beam attenuation. Technological advances have increased the clinical applications of these devices causing the Brazilian technologicalpark presenting a wide variety of scanners. Dose reduction strategies are difficult to implement because of the proper guidance lack on computed tomography examinations. However, these devices present possibilities of acquisition parameter adjusts according to the patients physical prole and diagnostic application for which it is intended the scan. The knowledge of the dose distribution is important when thinking about changes of image acquisition parameters aiming at reducing the dose. In this work, was used a cylindrical head phantom made of PMMA with openings that allow dose measurement in 5 regions. In three CT scanners, two GE and one Philips, with 64, 4 and 16 channels respectively, the central slice of the head phantom was irradiated and the doses were measured using a pencil ionization chamber. Radiochromic lm strips were placed in the peripheral and the central region of the head phantom and was performed scans of 10 cm in the phantom central region. The phantom scans were performed using protocols with diffierent voltages. After scanning, the radiochromic lm strips were digitalized and their digital images were used to have the dose longitudinal proles. The results compare the dose index values obtainedby the pencil chamber measurement with the dose longitudinal proles recorded by the lm strips. The dose index values found are in the range of 23.14 and 32.21 mGy. Values that are within the maximum limit recommended by Brazilian law. Noise analyzes were performed on the images of the central slice of the head phantom for each level of tension.The noise index values are in the range of 0.36 and 9.50 %. An optimized protocol was proposed for the head CT scan in one CT scanner with 80 kV tube voltage for images with a noise index of 0.5 %. The images were within acceptable parameters in radiodiagnosis.